UMPSA wins 2 gold medals in 18th Malaysia FIRA RoboWorld Cup 2025 - Hamdan, Daniyal (UMPSA, 2025)
MELAKA, 25 June 2025 – The robotics team from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) succeeded in winning two gold medals in the 18th Malaysia FIRA RoboWorld Cup 2025 held from 21 to 26 June 2025 at Politeknik Merlimau Melaka.